LIBERAL THINKING IN SALAF PESANTREN, IS IT POSSIBLE? (FREEDOM OF THOUGHT THE SANTRI MA’HAD ALY SUKOREJO, SITUBONDO) - Marjuni Marjuni; Moch. Khafidz Fuad Raya (Jurnal Tatsqif, 2021)
The existence of Ma’had ‘Aly is an exciting thing and brings a narrative of controversy. Since being legalised in 2002, Ma’had ‘Aly has transformed into a modern Islamic educational institution under the auspices of a traditional Salaf pesantren. This article aims to explain Ma’had ‘Aly as an Islamic educational institution that specifically (takha??u?) produces fiqh experts and supports freedom of thought in exploring Islamic law. The research method uses a qualitative approach by studying documents extracted from the history of Ma’had ‘Aly, the takha??u? curriculum, and the Tanwirul Afkar (TA) bulletin. The results reveal the integration of the Ma’had ‘Aly curriculum, which is combined with the general curriculum and contemporary scriptures. Second, the controversy over TA as a forum for students to manifest their competence as fuqaha on various developing issues. Some of the controversial issues decided by TA were allowing interfaith marriages, allowing non-Muslim Indonesian President elections, and similarities between Islam and Christianity in relations and history. Some realities above show that Islamic liberal thought has emerged in salaf pesantren through Ma’had ‘Aly. The contribution of this research provides novelty that apparently Ma’had ‘Aly is trying to show that the door of ijtih?d in the excavation of Islamic jurisprudence is still wide open.